Manajemen Berbasis Sekolah Dalam Peningkatan Kompetensi Keahlian Siswa Jurusan Teknik Kendaraan Ringan - Prima, Jaka; Siswanto, Romi (Andragogi: Jurnal Pendidikan dan Pembelajaran, 2023)
The purpose of this study in general is to find out the activities of the teaching staff management process in increasing professional competence at SMK PALAPA Mojokerto. This research uses qualitative research and case study design. Data collection techniques used in this study were interviews, observation and documentation. In data analysis, the researcher used Philipp Mayring's content analysis approach and Mills & Huberman's approach. The substantive findings of this study are (1) Curriculum Management and Competency management expertise in learning programs for both teachers and students (2) Student management in order to improve student competency skills of students majoring in TKR in forming students who are ready to work through additional activities and practical hours; students are given Islamic religious values such as reading walqiah, BTQ, praying in congregation so that the quality of education really meets what is expected both for the students themselves and when they work amid society. (3) Facility and Infrastructure Management. School facilities and infrastructure are one of the components in the school system. therefore its existence must be in harmony with other components. in increasing the competency skills of the PALAPA Mojokerto Vocational School students provide additional hours for students and increase field work practices for students so that they are able to be competitive and able to keep abreast of existing developments. Because besides us working with several MOU companies such as PT, CV, the school has also created a Special Job Exchange (BKK) which is an institution formed to support the competency skills of students majoring in TKR.